TORU WATANABE’S LOVE FOR NAOKO AND FOR MIDORI KOBAYASHI IN “NORWEGIAN WOOD” BY HARUKI MURAKAMI = TÌNH YÊU CỦA TORU WATANABE VỚI NAOKO VÀ MIDORI KOBAYASHI TRONG TIỂU THUYẾT “RỪNG NAUY” CỦA HARUKI MURAKAMI - Lê, Phương Mai (2021)
With an investigation into the novel “Norwegian Wood” by Haruki Murakami, the study aims at: (1) finding the discrepancies between Toru Watanabe’s love for Naoko and for Midori Kobayashi and (2) analyzing the reasons why Toru Watanabe struggles in love. Based on “The Triangular Theory of love” by Robert J. Sternberg and other theories of love as well as Sigmund Freud’s theory of human psyche, the researcher would examine the aforementioned issues deeply. The result reveals that Toru Watanabe’s love for Naoko is Consummate love while that for Midori is Romantic love, and Toru’s love for Midori can be considered more promising than that for Naoko. Additionally, Toru fights himself in love, as he has a struggling Ego; moreover, it is also because simultaneously he loves both Naoko and Midori and cannot decide whom to fully embrace.